Innate Immunity in Health and Disease 2021
DOI: 10.5772/intechopen.95248
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine of Autoimmune Diseases

Abstract: Genomic-based information is an essential key to precise therapy referred to as personalized medicine. Its application in autoimmune disease treatment will bring the required breakthrough in medicine. Autoimmune diseases are the disease conditions where the body’s immune system recognizes and generate an immune response against self-antigens. There exist different approaches of which precision medicine data can be utilized in the clinical management of autoimmune diseases; this includes diagnosis, prognosis, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Genomic data is an important data in precision medicine. Therefore, most thyroid diseases such as autoimmune thyroiditis are known to have high heritability [8,9]. Studies have reported high rate of Graves' disease in monozygotic twins compared to dizygotic twins (in the range of 50-70%, compared with 3-25% respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic data is an important data in precision medicine. Therefore, most thyroid diseases such as autoimmune thyroiditis are known to have high heritability [8,9]. Studies have reported high rate of Graves' disease in monozygotic twins compared to dizygotic twins (in the range of 50-70%, compared with 3-25% respectively).…”
Section: Introductionmentioning
confidence: 99%